The Relationship of Islamic Law and Ethics in Pharmacist Practice: A Literature Review - Ricky Aditya Syam; Tifan Adji Hutama; Istiara Subekti; Arwana Nareswara; Fathatul Bariyah; Rizky Aulia (Walidem Institute and Publishing, 2023)
This study examines the relationship between Islamic law and pharmaceutical practice, focusing on the necessity of meeting the criteria of halal and purity in pharmaceutical products for Muslim patients. In this context, pharmacists are essential in ensuring that medical practice meets professional standards and harmonizes with Muslim patients' religious and cultural beliefs and values. The study used a qualitative approach to collect and analyze data from various sources, including interviews with pharmacists and Muslim patients and literature reviews on pharmaceutical ethics and Islamic law. The results showed a gap in knowledge and awareness among pharmacists about halal principles in pharmacy. This often causes discomfort and concern among Muslim patients who are worried about the halal medicine they are taking. The study also found that better training and education on Islamic law and pharmacy could improve the quality and trustworthiness of Muslim patients' care in the health system. This research suggests the need to develop pharmaceutical guidelines that consider aspects of halal and Islamic law and ongoing training for pharmacists to improve understanding and service to Muslim patients. As such, this research contributes to inclusive and culturally sensitive pharmaceutical practices.